Clinical Usefulness of High-Sensitivity C-Reactive Protein in Predicting Risk of the Metabolic Syndrome: Epidemiologic Evidence - Song, MD, ScD, Yiqing (North American Journal of Medicine and Science, 2008)
C-reactive protein (CRP) is an acute-phase protein, which is primarily synthesized in the liver. In response to most forms of inflammation, infection, and tissue damage, plasma levels of CRP in human body may rise rapidly and markedly, as much as 100 or 1000-fold or more during the acute phase. In epidemiological studies, CRP levels well below the conventional clinical upper limit of 10 mg/L (as measured by high sensitivity CRP) have consistently been predictive of cardiovascular disease1,2 and type 2 diabetes in various populations.3 The “high sensitivity” refers to the lower detection limit of the assay procedures being used than previous commercial assays routinely used for clinical measurements.4 Highly sensitive assays for CRP are widely used in epidemiologic studies to precisely measure values within the range less than 10 mg/L. High-sensitivity CRP thus has become a clinically useful marker oflow-grade chronic inflammation. Low-grade chronic inflammation may be one of the common antecedents underlying the clustering of obesity, impaired glucose tolerance, dyslipidemia, and hypertension, known as the metabolic syndrome. Ranges of <1, 1 to 3, and >3 mg/L, which correspond to approximate tertiles of the CRP distribution in healthy US adults, are used to denote low-, moderate-, and high-risk cardiovascular groups. Of note, CVD and type 2 diabetes are the major sequelae of the metabolic syndrome. CRP independently predicts both CVD and type 2 diabetes, but it is unknown whether CRP evaluation is a valuable addition to the metabolic syndrome for risk assessment of CVD and diabetes.